A narrative inquiry of storytelling: a learning strategy for nursing students to reflect on their interactions with patients. Issue 2 (4th March 2022) - Timpani, Susan; Sweet, Linda; Sivertsen, Nina
ABSTRACT: Arts-based learning in the context of clinical placement is rarely discussed in the literature, yet storytelling is potentially a valuable tool for students to reflect on the multi-dimensional experience. Clandinin and Connolly's approach to narrative inquiry provided the methodology to explore students' experiences of storytelling as a learning strategy. Narrative inquiry is a relationship-based methodology, used to study the nature of people's experience. The approach is like that of clinical facilitators who work collaboratively with students to understand and provide mentorship through placement experiences. Creative writing and storytelling sessions with students were conducted throughout placement. Data included creative writing, oral stories, and researcher journal entries, collected over six placement blocks with 26 nursing students. Analysis identified that students engaged enthusiastically with storytelling; stories highlighted moments of student-patient interactions; the value of a positive clinical facilitator-student relationship; the complexity of registered nurse-student relationships; and students from cultural and linguistic diverse backgrounds experienced feelings of isolation from staff. The simple tools of pen and paper were a powerful medium for students to reflect on their interactions with patients. Facilitating the process of storytelling provided the researcher with insight into intrinsic and extrinsic obstacles and opportunities which may impact students' engagement with patients.